What Is the Role of AI in Age-Related Disease Prevention? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
As the global population ages at an unprecedented rate, the prevalence of age-related diseases such as cardiovascular conditions, respiratory illnesses, and ...
Keywords: AI in Geriatrics; Age-Related; Disease; Prevention; Artificial Intelligence; Machine Learning; Deep Learning